3D cuboidal vanadium diselenide embedded reduced graphene oxide hybrid structures with enhanced supercapacitor properties. Issue 1 (5th December 2016) - Marri, Subba R.; Ratha, Satyajit; Rout, Chandra Sekhar; Behera, J. N.
Abstract : Hydrothermal synthesis of VSe2 /reduced graphene oxide (RGO) has been reported and its supercapacitor performance was evaluated in a typical CR2032 coin cell setup. A specific capacitance of 680 F g −1 and an ultra-high energy density of 212 W h kg −1 were achieved. Abstract : The electrochemical supercapacitor performance of a VSe2 –reduced graphene oxide (RGO) hybrid has been reported for the first time. The hybrid was synthesized via a one-step hydrothermal route at different concentrations of graphene oxide, i.e. 0.15, 0.3, and 0.75 wt%. Enhanced supercapacitor performances were observed in the case of the hybrid obtained at 0.3 wt% of GO. It showed a specific capacitance of ∼680 F g −1 at a mass normalised current of 1 A g −1 which was ∼6 and ∼5 fold higher than those of bare VSe2 and bare RGO, respectively. Furthermore, a high energy density of ∼212 W h kg −1, power density of ∼3.3 kW kg −1, and ∼81% retention of the initial capacitance even after 10 000 cycles of charge–discharge were observed.